Global shift towards stakeholder-oriented corporate governance? Evidence from the scholarly literature and future research opportunities - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2021)
Purpose: By reviewing prior scholarly corporate governance (CG) literature and a review of more recent stakeholder studies, this paper aims to examine the extent to which stakeholders and their interests have gained in importance in recent years compared to the shareholder approach, which is dominant in many national economies and suggest future research opportunities. Design/methodology/approach: This study conducts a literature review to examine major findings in prior studies. Findings: The reviews and analyses provide support for a formal and informal convergence of CG systems towards more stakeholder-oriented elements globally. In general, at the institutional and firm levels, there are remarkable shifts to adopt stakeholder-oriented rules and practices. However, there is limited evidence that all these trends will actually lead to full convergence towards a single stakeholder-oriented governance model. Originality/value: The paper offers an extensive summary of prior studies that investigate the impact of CG on firm stakeholder-orientation and social performance. Based on the review, this study suggests promising research directions.